Leadership standards in action: The school principal as servant leader - Ervin, Candice (Journal of Interdisciplinary Studies in Education, 2015)
Leadership as a school principalcan be an arduous task. Despite thelaborious mood that a principal mayexperience, the career is very rewarding.In order for one to know how to becomean effective principal he or she mustunderstand and apply certain standardsto their professional title. In CadeBrumley’s Leadership Standards inAction: The School Principal as ServantLeader, he discusses and explores theidea of being a servant leader. Heexplains to readers the idea of servantleadership by utilizing the InterstateSchool Leaders Licensure Consortium(ISLLC) standards and personalaccounts of current principals. Brumleyoffers an enlightening perspective tocurrent and potential leaders through hiscreative narration of realistic situations.